Ultrafast structural dynamics of carbon–carbon single-bond rotation in transient radical species at non-equilibrium - Seonggon Lee; Hosung Ki; Donghwan Im; Jungmin Kim; Yunbeom Lee; Jain Gu; Alekos Segalina; Jun Heo; Yongjun Cha; Kyung Won Lee; Doyeong Kim; Jeongho Kim; et al. (Nature Communications)
Abstract Bond rotation is an important phenomenon governing the fate of reactions. In particular, heterogeneously substituted ethane derivatives provide distinct structural conformations around the bond, empowering them as ideal systems for studying the rotation along carbon-containing single bonds. However, structural dynamics of ultrafast single-bond rotation, especially along C–C• bonds, have remained elusive as tracking the detailed changes in structural parameters during the rotational isomerization is challenging with conventional spectroscopic tools. Here, we employ femtosecond time-resolved X-ray liquidography to visualize the rotational isomerization between anti and gauche conformers of tetrafluoroiodoethyl radical (C2F4I•) and 1,2-tetrafluorodiiodoethane (C2F4I2), simultaneously. The TRXL data captures perturbations in conformer ratios and structures of each reacting species, revealing that the rotational isomerization of C2F4I• and C2F4I2 follows anti-to-gauche and gauche-to-anti paths with time constants of 1.2 ps and 26 ps, respectively. These findings also align with the computational predictions. This work offers an atomic-level insight into the kinetics and structural dynamics of single-bond rotation.